IDEA OF STATE REGULATION OF HOTEL ACCOMMODATION PRICES IN BULGARIA AND THE PRINCIPLE OF FREE ECONOMIC INITIATIVE - VIEWS AND SOLUTIONS - Yoncheva, Tanya (The Business of Tourism, 2025)
After the transition from a centralized to a free market economy in Bulgaria, market mechanisms, competition, private ownership and private entrepreneurship dominate the different sectors of the national economy. In a relatively short period of time in the tourism sector many private business entities emerged and established themselves, developing their activities in the highly competitive and rapidly developing tourism market. The State has now moved away from its dominant position in economic relations, but its presence in the tourism sector remains. It is still the responsibility of the state authorities to formulate and implement the overall tourism policy and the established strategy for the sustainable development of this important sector of the Bulgarian economy. These same state bodies, in the person of the Ministry of Tourism, are also entrusted with the immediate functions of organising and administering individual tourism activities and constantly monitoring their lawful exercise. The question to what extent and with what intensity is state interference in the functioning of the tourism sector permissible and where is the boundary between regulation and subordination of an economic activity has many facets and is unlikely to receive a clear-cut answer. This article examines the issue at hand through the prism of a specific administrative proceeding before the Commission for Protection of Competition. The Commission has been asked by the relevant ministry to issue an opinion on the compatibility of the draft introduction of minimum room rates in hotels with the competition rules. The observations and arguments of the interested parties are set out below. The author’s personal views on the case are set out.